Characterization, Concentration and Utilization of Sweet and Acid Whey - Alsaed, Ali K.; Ahmad, Rafat; Aldoomy, Hayder; El-Qader, Salma Abd; Saleh, Duaa; Sakejha, Haneen; Mustafa, Laila (Pakistan Journal of Nutrition, 2013)
Normal acid and sweet whey samples were collected from six national dairy plants located in Amman city. They were characterized physico-chemically. The whey was concentrated using vacuum scraper concentrator; the concentration process was optimized with regard to several variables. The concentrated whey either acid or sweet were obtained and evaluated organoleptically with regard to color, flavor and consistency. Accordingly, the optimum concentration treatment was chosen, characterized physico-chemically and used for further research work. The obtained results revealed that the Concentrated Acid Whey (CAW) had more dry matter (68.98%), acidity (4.95%) and salt (14.56%) compared with the Concentrated Sweet Whey (CSW). On the other side, CSW had more lactose (36.40%) and protein (8.25%) compared to CAW. CAW had a better stability or shelf life than that of CSW due to its lower water activity (0.35). The concentrated whey was relatively rich in many minerals and trace elements i.e Na, K, Ca and Mg. Consumption of 50 g of CAW when used as a sugar replacer in bakery and confectionery items will contribute 114, 34, 25, 22, 20 and 18% of the recommended daily intakes of Na, Zn, Cu, Ca, Mg and K respectively. The mineral composition data as well as the sensory evaluation results reflected the unlimited benefits that can be achieved by concentrating acid and sweet whey and there incorporating in formulating some bakery and confectionery items. The addition of acid whey solids to the three studied items i.e cookies, spongy cake and bread improved their quality parameters specially flavor, color and texture.